Vibration-Induced Stress Analysis Of Natural Gas Vehicle - Abu Mansor, Siti Marhainis (2008)

(untitled)
The automotive industry has been exploring alternative vehicle fuel for decades as petrol reserve for the future is reducing. Natural gas is found to be the most suitable alternative choice, but the natural gas storage tank that is to be located in the vehicle requires specific space. Thus, a dedicated natural gas vehicle platform is designed and during the initial design stage of vehicle platform, the study of the self-excited vibration and the affected stress to the vehicle platform structure were analyzed. There have been little studies about the effects of the vehicle structure natural frequency to the structural stress. Vibration is known as a source of energy that induces structural and mechanical oscillations, self-excited vibration is an unwanted occurrence. Other than resonance, high stresses caused structural failure thus their values are investigated. In this research, there are three models of compressed natural gas (CNG) vehicle platforms designed from the modification of the conventional petrol fuelled PROTON Waja’s vehicle platform and they are CNG 3T, CNG 4T and CNG 5T Platforms. Finite element analyses were done to these platforms models with the conventional petrol fuelled platform being the benchmark platform. The modal analysis in searching for the natural frequency values below 50Hz are performed first and the induced stresses due to the natural frequency mode shape deformation is determined through static analysis. The frequencies, mode shape and vibration-induced stress results for all the analyzed platforms are presented. The analysis results showed that the CNG 3T, CNG 4T and CNG 5T Platforms have a maximum stress of 53.3MPa, 36.0MPa and 43.9MPa accordingly when induced by natural vibrations of frequencies below 50Hz. The maximum stresses are below the yield stress of the applied material. The natural vibration mode shape have been identified to be the main factor of the induced stresses, while the platform’s geometry has affected the natural vibration frequency values as the modifications made has increased the platform’s stiffness. However, the relationship between frequency and the induced stress could not be determined due to the inability to predict the natural vibration mode shape that has been the main factor of the vibration-induced stress analysis. Nevertheless, the results obtained will serve as a base for future vibration-induced stress study to structures.